PENGARUH DIMENSI DIMENSI KEADILAN ORGANISASI TERHADAP KEPUASAN KERJA - Endang Sri Wahyuningsih; Heri Setiawan (FEB UNWIKU PURWOKERTO, 2021)
This research is entitled The Effect of Dimensions of Organizational Justice on Job Satisfaction (case study at PD BPR Purwokerto). The purpose of this study is to determine and analyze the significance of the effect of distributive justice, procedural justice, interactional justice on job satisfaction of employees of PD BPR BKK Purwokerto. The analysis technique uses multiple linear regression. Based on the results of regression analysis, it is obtained that the tcount of the variable of distributive justice is greater than the t-table, the t-count of the procedural justice variable is greater than the t-table, and the t-count of the interactional justice variable is greater than the t-table value. The implication is that management needs to prioritize various policies related to variables of Distributive Justice, Procedural Justice and Employee Interactional Justice. One way to do this is by conducting job training programs for employees on a regular basis, creating a work atmosphere that is able to encourage employee self-confidence related to their ability to exercise control over themselves and the environment around them, and strive to meet various needs and expectations. employees related to the implementation of their duties and jobs effectively and efficiently